Effectiveness of Web-based Parenting Intervention in Improving Mindful Parenting among Parents of Elementary School Aged Children - Arri Handayani; Padmi Dhyah Yulianti; Ellya Rakhmawati (Kuras Institute, 2026)
The complexity of parenting in the current digital era requires web-based intervention innovation to provide attentive care that impacts the quality of care. This study examined the effectiveness of a web-based parenting intervention in improving mindful parenting among parents of elementary school–aged children. Fifty-seven participants joined the intervention program with parent-population characteristics (fathers and mothers) living with children aged between 7 and 12 years old. The instrument consisted of pretest-posttest mindful parenting scale. This quasi-experimental research used one group pretest-posttest group design. The results indicate a substantial enhancement in mindful parenting scores post-intervention (Z = −3.544; p = 0.000), with the average score increasing from 2.735 to 2.889. A Cohen’s d of 0.44 indicates a moderate effect size with meaningful practical significance. Dimension-level analyses reveal significant improvements in three dimensions listening with empathy, understanding and acceptance, and self-regulation. In the other two dimensions, namely emotional regulation and compassion, did not show significant changes. The understanding and acceptance dimension exhibits the greatest impact, with the highest mean increase and the largest effect size (d = 0.638). These findings indicate that the web-based intervention effectively enhances the cognitive aspects of mindful parenting but remains less optimal in addressing affective components that require more intensive emotional practice. This study offers important implications for the development of digital parenting programs and provide directions for future intervention research.